Experience XSI 4 the official Softimage XSI 4 guide to character creation - Sims, Aaron; Isner, Michael; Gale Group (Boston, Mass. Thomson Course Technology PTR, 2004)
This book will help you understand and work with XSI 4 to create a highly detailed character in a production environment. The approach in this book is unique because it is the result of a collaboration between art and technology.
Introduction -- Chapter 1. The interface -- Chapter 2. Designing and modeling a character -- Chapter 3. Texturing your character -- Chapter 4. Character setup -- Chapter 5. Animating your character -- Chapter 6. Scripting in XSI -- Chapter 7. Lighting, rendering, and compositing your character -- Chapter 8. Making crowds and character logic with behavior -- Image gallery -- Index.
Electronic reproduction.
Keywords: Microsoft Softimage 3D.; Computer animation; Three dimensional display systems; Electronic books